Underwater acoustic emission monitoring – Experimental investigations and acoustic signature recognition of synthetic mooring ropes. (June 2017) - Bashir, Imran; Walsh, Jodi; Thies, Philipp R.; Weller, Sam D.; Blondel, Philippe; Johanning, Lars
Abstract: Mooring ropes are essential components of offshore installations, and synthetic ropes are increasingly preferred because of their favourable cost to weight ratios. In-service condition of these materials is traditionally monitored through costly visual inspection, which adds to the operating costs of these structures. Acoustic Emissions (AE) are widely used for condition-monitoring in air, and show great potential underwater. This paper investigates the AE signatures of synthetic mooring ropes subjected to sinusoidal tension-tension loading in a controlled environment, using a large-scale dynamic tensile test rig. With a linear array of 3 broadband (20 Hz to 50 kHz) hydrophones, four main signatures are identified: low-to high frequency, low-amplitude signals (50 Hz to 10 kHz), low-amplitude broadband signals (10 kHz to 20 kHz), high amplitude signals (10 Hz to 48 kHz) and medium-amplitude signals (500 Hz to 48 kHz). These AE types are related to different stages of rope behaviour, from bedding-in to degradation and failure. The main findings are that the failure location and breaking load can be identified through the detection of AE. The occurrence of high amplitude AE bursts in relation to the applied tensile load allows the detection of an imminent failure, i.e. prior to the failure event. These initial results indicate that AE analyses can enable the integrity of synthetic mooring ropes to be monitored.